Family Health Tasks Implementation and Medication Adherence of Pulmonary Tuberculosis Patients: A Correlational Study - Tintin Sukartini; Nora Dwi Purwanti; Herdina Mariyanti (Jurnal Ners, 2020)
Introduction: Non-adherence medication is found among patients with pulmonary tuberculosis. Various factors influence patient adherence to medication. The purpose of this study was to analyze the relationship between family health tasks to medication adherence among patients with pulmonary tuberculosis.Methods: The design of this study was cross-sectional, with 45 sample size of pulmonary tuberculosis patients at Polyclinic of Pulmonary Disease in Haji General Hospital Surabaya taken by using a purposive sampling technique. Independent variables of this study were family health task which includes five dimensions, recognizing the family member health problem, making decisions for appropriate treatment measures, caring for sick family members, modifying the healthy environment and utilizing the healthcare facilities. The dependent variable was medication adherence. Data were taken using the questionnaires then analyzed by Spearman rho test.Results: There was a relation between tasks of family health: recognizing the family member health problem (p=0.001), taking decisions for appropriate treatment measures (p=0.000), caring for sick family members (p=0.003), modifying the healthy environment (p=0.006), and utilizing the healthcare facilities (p=0.001) with medication adherence in patients with pulmonary tuberculosis.Conclusion: The research of this study suggests the hospital arrange health education for the family and the patient to increase the quality of health services. The family can provide a conducive environment for the patient and further research can develop better research by using other methods such as direct observation, demonstration, and simulation.